Achmea, Kramer and Disconnection Clauses. EU Legal Regionalism in Action - Láncos, Petra Lea (Review of European and Comparative Law, 2024)
Over the past decades, the European Union has been gradually developing and maintaining legal regionalism within its jurisdiction. Its purpose is to preserve the achievements of integration, as well as the unity and autonomy of EU law. In this paper, I recount the toolbox of EU legal regionalism from primary law, through the case law of the Court of Justice of the European Union, to the institution of the so-called disconnection clauses employed by the EU in certain international treaties, expanding also on their possible effects on international law and the Member States’ relations with third parties.